On the Series of +CG Lightning Strokes in Dancing Sprite Events. Issue 19 (12th October 2018) - Bór, J.; Zelkó, Z.; Hegedüs, T.; Jäger, Z.; Mlynarczyk, J.; Popek, M.; Betz, H. D.
Abstract: In dancing sprite events, sprite entities and groups appear in rapid succession together with a corresponding series of parent lightning strokes. Dancing sprite events, including a case with possible sprite rebrightening, were recorded on video simultaneously from two observation sites above a mesoscale convective system in Central Europe on the night of 6 August 2013. Joint analysis of triangulated locations of sprite elements, position, type, and peak current of lightning strokes from the LINET lightning detection network database and current moment waveforms deduced at the Hylaty station, Poland, showed that subsequent sprite‐parent lightning strokes occurred no further than 21 km from the closest preceding sprite entity in the cases analyzed in this study. Additionally, it was found that longer sprite delay times tend to correspond to larger sprite location offsets from the parent +CG stroke. These observations, the occurrence of +CG lightning stroke and sprite sequences, as well as sprite‐sprite delay times and displacements can be explained if +CG strokes are part of one extended lightning flash. A corresponding production mechanism based on previous findings on the formation of sprite‐producing and general +CG lightning discharges is suggested. Plain Language Summary: In dancing sprite events, sprites appear in rapid succession together with a corresponding series of parent lightning strokes. Dancing sprite events were recorded on video simultaneously from two observation sites above an extended thunderstorm system in Central Europe on the night of 6 August 2013. Comparison of triangulated sprite locations and the locations of corresponding lightning activity revealed that subsequent sprite‐parent lightning strokes occurred below or relatively near the location of the closest preceding sprite entity in the examined cases. In this paper, a mechanism is suggested for the development of lightning flashes that produce dancing sprites. The proposed mechanism accounts for prompt and delayed sprites relative to their parent lightning stroke, highlights the role of the variation of lightning current in sprite production, and can explain the observed closeness of the next +CG lightning stroke to the area of previous sprites. Key Points: The observations support that dancing sprite events tend to occur above stratiform cloud areas If a sprite is up to 45 km away from its parent +CG stroke, the offset of the next sprite in the same sequence was found to be larger It is suggested that +CG parent strokes in dancing sprite events are often part of one extensive lightning flash